Definite and Indefinite Use in Ronaldo’s Interview - Diffyanie Diffyanie; Ambalegin Ambalegin (Prosiding, 2023)
This qualitative research aimed to find out the errors of definite and indefinite in Ronaldo’s interview. The result of this research was displayed descriptively. The researchers used qualitative method for this research. The observational method and technique was a non-participant used to collect the data. While analyzing the data, identification was used as the method and competence in comparing was used as the technique. The script of Ronaldo’s interview was taken as the data and were analyzed narratively. Ronaldo as the speaker used “the” which he was not referring to a specific noun. He also used to talk about something that referred to a wide range of things then he suddenly used “the” when “the” only referred to something specific thing or a single thing or noun. This research used the theory of ​Hewings (2013). The results showed that 20 data errors of definite and indefinite use. It showed the errors of definite with 15 data and indefinite with 5 data.